Utility of quantitative magnetic resonance angiography and non-invasive optimal vessel analysis for identification of complications and long-term hemodynamic changes in post-pipeline embolization patients. Issue 4 (August 2022) - Ryu, Brendan; White, Timothy G; Shah, Kevin A; Turpin, Justin; Link, Thomas; Dehdashti, Amir R; Katz, Jeffrey M; Black, Karen; Woo, Henry H
Introduction: Quantitative magnetic resonance angiography and non-invasive optimal vessel analysis serve as powerful tools to collect and analyze hemodynamic data from pipeline embolization patients. At our institution, patients receive post-embolization quantitative magnetic resonance angiography within 24 h of treatment and within 6 months for follow-up to evaluate pipeline patency. Here, we aim to elucidate the long-term hemodynamic changes following pipeline embolization device placement and report two cases in which in-stent stenosis was detected. Methods: Medical records of patients who underwent pipeline embolization device placement for an internal carotid artery aneurysm between 2017 and 2019 were reviewed. Patients who received post-procedure NOVA and follow-up NOVA were included in the study ( n = 32). Location and size of aneurysm, number of pipeline embolization device deployed, and complications were collected along with the non-invasive optimal vessel analysis report (flow volume rate (ml/min), mean, systolic, and diastolic flow velocities (cm/s), and vessel diameter (mm)). Internal carotid artery vessel flow rate was measured proximal to the pipeline embolization device. Derivations of hemodynamic parameters (pulsatility index, Lindegaard ratio, and wall shear stress) were calculated. Results: The middle cerebral artery mean and diastolic flow velocities were significantly lower on the follow-up NOVA compared to the post-procedure NOVA. Moreover, follow-up NOVA demonstrated lower middle cerebral artery wall shear stress on the side with flow diversion compared to the post-procedure NOVA. In-stent stenosis, requiring intervention, was detected in two patients on follow-up NOVA. One patient had a successful balloon angioplasty of the stented internal carotid artery that resolved her stenosis. However, the second patient developed progressive stenosis and expired despite intervention. Conclusion: Long-term hemodynamic adaptations post-pipeline embolization device demonstrate decreased wall shear stress and decreased mean and diastolic flow velocities in the distal middle cerebral artery, which suggest decreasing velocity of blood flow with endothelialization of the device. Furthermore, follow-up NOVA is a useful tool for detecting potential flow-related complications such as in-stent stenosis.